Programma: 16-19 oktober Carlos Trafic, Bamsisters; 23-26 oktober Sidewalk Theatre, Carlos Trafic (1976)
Programma: 16-19 oktober Carlos Trafic, Bamsisters; 23-26 oktober Sidewalk Theatre, Carlos Trafic.